Landasan Kurikulum Indonesia dalam Sistem Pendidikan dengan Studi Literatur - Handayani, Sri; ‘Ainy, Mustachsana Qurrotu; Iftitiyani, Warohmah; Khuriyah, Khuriyah (TSAQOFAH, 2024)
The curriculum is a main element in education that influences all educational activities. With its very important strategic role, curriculum development must be carried out carefully and not haphazardly. This process requires a solid foundation, supported by thorough research and deep thinking. This research aims to understand the foundations of curriculum development in Indonesia. In general, four foundations will be discussed in this study, namely the philosophical foundation, psychological foundation, sociological foundation, and organizational foundation. The method used is literature study. This research is a type of study that collects data from literature. The data collection technique in this research is documentation, which involves searching for written sources that contain information on the discussed topic. Primary data is obtained from reading references such as books, journals, and websites. Philosophical foundations, philosophical views are very much needed in education, especially in determining the direction and goals of education.The sociological foundation directs the study of the curriculum in relation to society, culture, and the development of knowledge. The organizational foundation pertains to the organization of material, which includes the scope of the material and the arrangement of each material, as well as the material as a whole, organized and arranged systematically according to the phases of physical-psychological growth and development of the learners based on in-depth and sufficiently comprehensive thinking. Curriculum developers must consider the psychological condition of individuals, in this case, the students, especially in designing and implementing the curriculum so that educational goals can be achieved optimally. Based on the explanation above, it can be concluded that there are four foundations for curriculum development, which include the philosophical foundation, sociological foundation, organizational foundation, and psychological foundation.